Achieving Pro-Environmental Attitudes Through Integration Of Entrepreneurial Values In Professional Teacher Education Students - Naila Marom Salsabila; Muh Sabandi (UNIVED Press, 2025)
Increased exploitation of nature and environmental damage are the sources of problems of biodiversity population in Indonesia. This phenomenon occurs with the role of integration of modern entrepreneurial values ​​based on desires through pro-environmental education of Teacher Professional Education (PPG) students in Indonesia. This study aims to analyze the effect of integration of green entrepreneurial values ​​through entrepreneurial organizations as mediation on pro-environmental behavior. The research approach used is a quantitative survey with a nonprobability sampling data collection method on 104 teacher professional education (PPG) students in Indonesia. Path model analysis using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results of the study showed a significant effect except for green leadership and green power management resources on pro-environmental behavior. In addition, the mediation of green entrepreneurial orientation also had an insignificant effect. These findings emphasize the urgency of the approach to integrating entrepreneurial values ​​to increase pro-environmental behavior in teacher professional education (PPG) students as prospective professional teachers.